Pengaruh Komite Audit, Audit Internal, Dewan Komisaris Independen Terhadap Kinerja Keuangan BUMN - Cindy Amelia Putri; Sofie Sofie (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to examine the effect of audit committee, internal audit, and independent board of commissioners variables on financial performance. The analytical method in this study uses a multiple linear regression analysis model using samples from State-Owned Enterprises companies listed on the Indonesia Stock Exchange in 2019-2021 and sampling using a purposive sampling method. The results of this study indicate that the audit committee and independent board of commissioners have no effect on financial performance, and internal audit has a positive effect on financial performance.